101PCombined cellular immunotherapy and chemotherapy improves clinical outcome and displays safety in the treatment of patients with colorectal cancer. (24th November 2019) - Wang, C; Xie, L; Wang, Y; Liang, T; Wu, H; He, H
Abstract: Background: Colorectal cancer (CRC) is the second leading cause of cancer-related death worldwide. Despite the availability of multiple treatment strategies, the prognosis of the patients with CRC is dismal. The aim of this study is to evaluate the efficacy and safety of cellular immunotherapy (CIT) (the use of autologous natural killer cells, γδTcells and cytokine-induced killer cells) in combination with chemotherapy in patients with CRC. Methods: A retrospective analysis of 377 patients with colorectal adenocarcinoma from December 2010 to December 2015 was performed, including 97 patients in the CIT+chemotherapy group and 280 patients in the chemotherapy group. The primary endpoints were DFS or PFS (Patients with adjuvant therapy after radical resection of colorectal cancer had the same DFS as PFS). The secondary endpoints were OS, ORR, DCR, adverse reaction rate and treatment tolerance. Results: The 3-year progression-free survival rate of CIT+chemotherapy group and chemotherapy group was 67.2% vs 53.9% (P < 0.01), and the 5-year OS rate was 74.1% vs 50.8% (P < 0.001). CIT+chemotherapy was independent prognostic factors for both DFS (HR: 0.618, 95% CI: 0.428–0.891) and OS (HR: 0.513, 95% CI: 0.335–0.784). The ORR and DCR of CRC patients with IV staging in the CIT+chemotherapy compared to chemotherapy group were 63.0% vs 50.8% (P = 0.291) and 81.5% vs 65.6% (P = 0.131) respectively. The percentage of CD3+, CD3+ CD4+ cell subsets were significantly increased from 70.11% to 75.87% (P < 0.01), and 42.53% to 44.39% (P = 0.02) in the CIT+chemotherapy group after treatment. Overall adverse reaction rate of CIT+chemotherapy group and chemotherapy group was 75.3% vs 75.4% (P = 0.98) respectively. In patients with stage III, the median chemotherapy course in CIT +chemotherapy compared to chemotherapy group is 8 vs 6 (P = 0.003). Conclusions: High quality and standardized CIT combined with chemotherapy can promote the survival time, reduce the recurrence rate and improve the immune status of CRC patients. In addition, it is safe and low-toxic which improves the patient's tolerance to chemotherapy. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.